1974
DOI: 10.7164/antibiotics.27.31
|View full text |Cite
|
Sign up to set email alerts
|

An in Vivo Pyelonephritis Assay for Screening Therapeutic Agents

Abstract: Eighty to 100°0 of mice stressed with an intraperitoneal dose of 200-240 mg bromoethylamine hydrobromide (BEA)/kg and infected intraveneously 72 hours later with Proteus mirabilis, Pseudomonas, Escherichia coli or Serratia host large numbers of bacteria in their kidneys 3-4 days post-infection.If death (probably due to uremic poisoning) does not intervene, the infection lasts for weeks. The therapeutic effects of carbenicillin and ampicillin were tested in this pyelonephritis model. Carbenicillin was effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1974
1974
1990
1990

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The presence of calculi has generally been regarded as a late complicating factor of the analgesic abuse syndrome and there appears to be no published data on the chemical composition of the urolithiases. In fact, the induction of urinary tract infection in rats is much easier after a BEAinduced RPN (Thiele, 1974) and if analgesics are given concomitantly (Vivaldi, 1968). Similar matrix changes, together with electrolyte wastage, mineralisation and recurrent urinary tract infection in human analgesic abusers may be relevant to the development of urinary calculi in this population.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of calculi has generally been regarded as a late complicating factor of the analgesic abuse syndrome and there appears to be no published data on the chemical composition of the urolithiases. In fact, the induction of urinary tract infection in rats is much easier after a BEAinduced RPN (Thiele, 1974) and if analgesics are given concomitantly (Vivaldi, 1968). Similar matrix changes, together with electrolyte wastage, mineralisation and recurrent urinary tract infection in human analgesic abusers may be relevant to the development of urinary calculi in this population.…”
Section: Discussionmentioning
confidence: 99%
“…As a model of hematogenous infection, several workers have used intravenous injections of the organism (5)(6)(7)(8)19), but the closeness of the kidney infection dose to the lethal dose makes this model difficult. To increase the susceptibility of the kidneys to P. aeruginosa, artificial manipulations such as administration of ferric sorbital citrate (2) or 2-bromoethylamine hydrobromide (26), massage of the renal parenchyma, thermocautery injury of the renal medulla, and ureteral ligation (23) have been performed before intravenous inoculation of the organisms. As a model of ascending infection, methods such as surgical implantation of a foreign body with inoculation of P. aeruginosa into the bladder (24), inoculation of the organism into the renal pelvis by transvesical ureteral catheterization (21), and inoculation of the organism into the obstructed ureter (14) have been used.…”
Section: Samentioning
confidence: 99%
“…To date, little work has been done with respect to the host-parasite relationships of this particular microorganism [3,11,13,14,16,20,25,29,30,31,38], It has been known for a long time that S. marcescens strains elaborate pathobiologically powerful endotoxins which are capable of eliciting generalized Shwartzman reactions [1,6]. Very recently, Q uarles et al [24] demonstrated dialyzable toxic products (maximal molecular weight 15,000) produced by a strain of S. marcescens that had been maintained in an ingeniously conceived goat artificial kid ney fermentor system; it was shown that when the population of bacterial cells had exceeded lO'/ml, and when the cells had reached the stationary phase of growth, the experimental animals became toxemic, leukopenic, and developed fever.…”
mentioning
confidence: 99%